Anticholinergic Drugs Interact With Neuroprotective Chaperone L-PGDS and Modulate Cytotoxicity of Aβ Amyloids - Low, Kimberly Jia Yi; Phillips, Margaret; Pervushin, Konstantin (Frontiers in Pharmacology, 2020)
Anticholinergic drugs can be used as a treatment for many diseases. However, anticholinergic drugs are also known for their cognition-related side effects. Recently, there has been an increasing number of reports indicating a positive association between exposure to anticholinergic drugs and Alzheimer's disease (AD). Our novel study provides evidence of interactions between two representative anticholinergic drugs [Chlorpheniramine (CPM), a common antihistamine, and Trazodone (TRD), an antidepressant] with neuroprotective amyloid-beta (Aβ) chaperone, lipocalin-type prostaglandin D synthase (L-PGDS) and the amyloid beta-peptide (1–40). Here, we demonstrate that CPM and TRD bind to L-PGDS with high affinity where chlorpheniramine exhibited higher inhibitory effects on L-PGDS as compared to Trazodone. We also show that the interactions between the drug molecules and Aβ(1–40) peptides result in a higher fibrillar content of Aβ(1–40) fibrils with altered fibril morphology. These altered fibrils possess higher cytotoxicity compared to Aβ(1–40) fibrils formed in the absence of the drugs. Overall, our data suggest a mechanistic link between exposure to anticholinergic drugs and increased risk of Alzheimer's disease via inhibition of the neuroprotective chaperone L-PGDS and direct modification of Aβ amyloid morphology and cytotoxicity.